About the impact of wind turbine wake vortices on helicopter trim and rotor blade motion - Wall, B.G. van der; Lehmann, P.H. (My University, 2017)
With increasing numbers of large wind turbines on-shore and off-shore, interactions of their wake with heli-copters become interesting. In this paper the wake is modeled as a tip vortex helix with a vortex strength estimated from the wind turbine thrust. Helicopter rotors of different size are subjected to the wake and the collective and cyclic controls required to keep the trim are compared to the maximum available controls of the rotorcraft. In addition the blade flapping response due to the vortex influence without pilot action is com-puted and compared to maximum flapping angles allowed. It is found that typical onshore wind turbines could be a hazard for ultralight helicopters, but not for larger helicopters. Large offshore wind turbines, how-ever, could even be a danger for small helicopters that may be used for maintenance. In addition the results are compared to fixed-wing wake vortex interaction with a helicopter as given in the literature.